Human health risks from heavy metals in fish of Buriganga river, Bangladesh - Kawser Ahmed, Md; Baki, Mohammad Abdul; Kundu, Goutam Kumar; Saiful Islam, Md; Monirul Islam, Md; Muzammel Hossain, Md (SpringerPlus, 2016)
Heavy metals are known to cause deleterious effects on human health through food chain. Human health risks were evaluated from consumption of heavy metal contaminated fish from Buriganga River in Bangladesh. Whole body of five fish species ( Puntius ticto, Puntius sophore, Puntius chola, Labeo rohita and Glossogobius giuris ) were analyzed which contained various concentrations of Cd, As, Pb, Cr, Ni, Zn, Se, Cu, Mo, Mn, Sb, Ba, V and Ag. Concentrations of Mn, Zn, Se and Pb in all fish species were above the Food Safety Guideline (FSG) by WHO/FAO. Assessment of noncarcinogenic health hazard by target hazard quotient (THQ) indicated no concern from consumption of these fish except for Mn. However, all metals together may affect human health as revealed by hazard index (HI). The target cancer risk (TR) values suggested carcinogenic risk from Ni and As. Taken together it can be concluded that there is potential human health risk in consuming fish from river Buriganga.